2013
DOI: 10.1123/japa.21.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Step Test for Exercise Prescription: No Extension to a Larger Age Range

Abstract: The purpose of this study was to determine the validity of a submaximal exercise test, the Step Test Exercise Prescription (STEP), in a broad age range and in individuals in the earliest stages of Alzheimer's disease (AD). Individuals (n = 102) underwent treadmill-based maximal exercise testing and a STEP. The STEP failed to predict peak oxygen consumption (VO2 peak), and was a biased estimate of VO2 peak (p < .0001). Only 43% of subjects' STEP results were within 3.5 ml × kg−1 × min−1 of VO2 peak. When catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…On the one hand, multiple studies are in support of the use of step tests to estimate VO 2max in healthy subjects (Montoye, ; Ryhming, ; Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Siconolfi et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ; Beutner et al ., ) while others are not (Buckley et al ., ; Vidoni et al ., ). Moreover, previous studies were limited by small sample sizes (<100 participants), inclusion of non‐representative samples (sportsmen, college students, participants ≥65 years) and inclusion of subjects with chronic disease and/or lack of measured VO 2max data (Montoye, ; Ryhming, ; Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ; Dal Corso et al ., ; Marcora et al ., ; Kuspinar et al ., ; Vidoni et al ., ). As a result, after thorough literature review, it becomes clear that VO 2max estimation equations from fixed‐rate step tests in healthy adults (between age 18–75 years) were insufficiently validated before execution of the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the one hand, multiple studies are in support of the use of step tests to estimate VO 2max in healthy subjects (Montoye, ; Ryhming, ; Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Siconolfi et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ; Beutner et al ., ) while others are not (Buckley et al ., ; Vidoni et al ., ). Moreover, previous studies were limited by small sample sizes (<100 participants), inclusion of non‐representative samples (sportsmen, college students, participants ≥65 years) and inclusion of subjects with chronic disease and/or lack of measured VO 2max data (Montoye, ; Ryhming, ; Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ; Dal Corso et al ., ; Marcora et al ., ; Kuspinar et al ., ; Vidoni et al ., ). As a result, after thorough literature review, it becomes clear that VO 2max estimation equations from fixed‐rate step tests in healthy adults (between age 18–75 years) were insufficiently validated before execution of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Even though some authors reported an acceptable VO 2max estimation when using step tests in healthy adults (Montoye, ; Ryhming, ; Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Siconolfi et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ; Beutner et al ., ), others reported a systematic under‐ or overestimation of VO 2max (Buckley et al ., ; Vidoni et al ., ). Moreover, these previous studies were limited by small sample sizes (<100 participants) (Sloan, ; Kasch et al ., , ; Jette et al ., ; Keren et al ., ; Stevens & Sykes, ; Chatterjee et al ., ; D'Alonzo et al ., ; Beutner et al ., ), inclusion of non‐representative samples (sportsmen, college students, participants ≥65 years), (Montoye, ; Ryhming, ; Sloan, ; Keren et al ., ; Stevens & Sykes, ; Petrella et al ., ; Chatterjee et al ., , ; D'Alonzo et al ., ), inclusion of subjects with chronic disease (Dal Corso et al ., ; Marcora et al ., ; Kuspinar et al ., ; Vidoni et al ., ) and/or lack of measured VO 2max data (D'Alonzo et al ., ; Kuspinar et al ., ). It follows that the validity of fixed‐rate step tests to estimate VO 2max in a larger group ( n > 100) of healthy subjects free from any chronic disease, and with a wide age range (between 18 and 75 years), still remains to be established.…”
Section: Introductionmentioning
confidence: 97%
“…The protocols for obtaining the original ( Y , VO 2 peak) and proxy ( X , STEP) measures were described in Vidoni et al (2013). While differences in the KU ADC Registry and REACH Laboratory measure collections differed slightly as described by Vidoni et al, these data provide a useful example for the statistical discussions presented here.…”
Section: Motivating Examplementioning
confidence: 99%
“…Model assessment by residual analysis was not further described nor their results presented as this was not the focus of the work presented here. More formal presentation of the motivating example results, including subgroup-specific assessments, was presented previously in Vidoni et al (2013). The alternative, paired t test approach was also performed for comparison.…”
Section: Motivating Examplementioning
confidence: 99%
See 1 more Smart Citation